On the magnetically driven ferroelectric phase in GdMnO3 - Ribeiro, J. L. (2008)
At room temperature, GdMnO3 is a paraelectric and paramagnetic with a distorted perovskite structure of orthorhombic symmetry (space group Pnma). On cooling, it undergoes a phase transition sequence to a magnetic incommensurate phase ( k = δ(T ) a∗; Tc1 = 42 K) and a A-type antiferromagnetic phase (Tc2 = 27 K). At low temperatures (T ≤ 12K), a magnetic field applied along the a-axis destabilizes the antiferromagnetic phase and induces a first order transition to a magnetic commensurate modulated phase ( k = 14 a∗) that is also ferroelectric ( P// c ). This work analyses this field induced phase transition from the point of view of the symmetry and Landau theory.